Parent and Teacher Ratings of Attention during a Year-Long Methylphenidate Trial in Children Treated for Cancer* - Netson, Kelli L. (Oxford University Press, 2011)
Objective Longitudinally examine attention performance in childhood cancer survivors prescribed methylphenidate (MPH) to ameliorate cognitive late effects, comparing measures for inter-rater and inter-method discrepancies. Methods Survivors of acute lymphoblastic leukemia (n = 33) or brain tumor (n = 35), mean age 11.11 ± 0.37 years, completed a 12-month, open-label trial of MPH. Conners’ Parent and Teacher Rating Scales were completed at baseline, 1, 3, 6, and 12 months. The Conners’ Continuous Performance Test (CPT) was completed at baseline and 12 months. Results Improved attention was reported after 1 month of MPH (p < .05), with relative stability throughout the trial. Inter-rater agreement was low-to-moderate (ICC = –.06 to .46). Observer ratings correlated with select CPT indices at baseline (p < .05), but not at 12 months. Conclusions Childhood cancer survivors’ attention improved after 1 month on MPH. Modest agreement between parents and teachers, and low-to-moderate correlations between behavior ratings and performance-based attention measures highlight a need for multimodal assessment.